Analisis Beban Kerja Karyawan Banquet di UNP Hotel and Convention - Aulia Mutia Giska; Hijriyantomi Suyuthie (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
The aim of this research is to significantly analyze the workload of banquet employees at UNP Hotel & Convention. The approach used in this research is descriptive qualitative. Interviews, observations and documentation were used for the data collection process. There were 6 respondents from UNP Hotel & Convention banquet employees. Data triangulation and interview reduction methods were used to analyze the data. The results of this research indicate that the workload of banquet employees is not optimal. It can be seen from the working conditions and the use of working time that have not been fully implemented properly according to the established Standard Operating Procedures. Companies can consider increasing the availability of banquet employees to create good performance.